Alcohol Misuse and Associated Risk Factors Across a Shipboard Deployment Among Active Duty US Navy and Marine Corps Personnel. (4th October 2017) - O'Malley, Christopher; Harbertson, Judith; Hale, Braden; Shaffer, Richard; Michael, Nelson; Scott, Paul
Abstract: Background: Alcohol misuse rates are elevated in the US military. Relevant longitudinal data are rare in deployed shipboard personnel. We examined the prevalence of hazardous and dependent alcohol misuse at 3 months prior to (T1), during (T2), and 3 months following (T3) deployment among shipboard US Navy and Marine Corps personnel. Methods: Data were collected from 11 local ships. Participants voluntarily completed anonymous surveys, including demographics, Alcohol Use Disorders Identification Test–Consumption (AUDIT–C), drug use, sexually transmitted infection (STI), and sexual risk behavior at T1, T2, and T3. Participants reporting age, gender, and ≥1 AUDIT-C response were included in the analysis. AUDIT-C scoring criteria were ≥3 for women and ≥4 for men (hazardous) and ≥8 (dependent). Data were analyzed using SAS software version 9.3. Proportions of alcohol misuse by time point were reported. Generalized regression model analyses assessed effects of main exposures after adjusting for demographic characteristics (statistical significance of P < 0.05). Generalized estimating equations were used when longitudinal data were included. Models included the longitudinal data's interaction with time. Results: Participants in the analyses were: T1 ( n  = 2, 593), T2 ( n  = 2, 010), and T3 ( n  = 1, 556). For T1, T2, and T3, respectively, 38.9, 39.4, and 42.4% screened positive for hazardous and 14.6, 12, and 10.8% for dependent alcohol misuse. Among those aged <21 years, 43.9, 49.3, and 35.4% screened positive for alcohol misuse at T1, T2, and T3, respectively. Longitudinal analysis showed those who screened positive for alcohol misuse were more likely to report an STI diagnosis (OR 2.4; 95% CI 1.44–4.01), exchange or receive money or goods for sex (OR 3.2; 95% CI 2.01–4.94), and use prescription or non-prescription drugs before sex (OR 2.1; 95% CI 1.64–2.61) than those who did not screen positive, after adjusting for other variables. Conclusion: Alcohol misuse was associated with STIs and sexual risk behaviors across deployment. Improved screening and intervention for individuals who misuse alcohol are needed among deploying shipboard personnel, which may result in a reduction of sexual risk-taking. Disclosures: All authors: No reported disclosures.